To be or not to be a platform worker? Lithuanian case in the context of EU countries - Miežienė, Rasa; Blažienė, Inga; Gruževskis, Boguslavas (Business: Theory and Practice, 2022)
The first wave of the COVID-19 pandemic, which peaked in 2020, and the unprecedented demand for home delivery services have led to the growth of platform work in many countries all over the world. The article analyses the situation of platform workers in the Lithuania’s labour market in the context of other EU countries. The paper presents the findings of a survey of platform workers carried out to define the social-economic picture of platform workers and identify their attitudes towards platform work in Lithuania. The survey has shown that the labour market situation of platform workers in Lithuania follows trends similar to other European countries in terms of socio-demographic characteristics, preferences and challenges. Slightly more significant differences between EU countries and Lithuania can be observed when analysing platform workers’ working time and earnings.